1996
DOI: 10.1111/j.2044-8295.1996.tb02610.x
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling learning from initial recall: The relationship between speed and memory deficits in old age

Abstract: Nettelbeck & Rabbitt (1992) found that measures of speed of performance with low knowledge requirements (four-choice reaction time, inspection time and coding-substitution) accounted substantially for age-related changes among 104 persons aged from 54 to 85 years in a number of more complex cognitive measures reflecting general fluid ability. However, the numbers of words recalled from a list after either a single brief viewing of each word, or following a cumulative learning procedure across four trials, prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 2 publications
1
12
0
1
Order By: Relevance
“…Thus, the relationship of age to performance on these tests was also not wholly secondary to changes in information-processing rate. The persistent relationship between age and the test of visuospatial paired associates learning is consistent with data reported by Nettelbeck and Rabbitt (1992) and by Nettelbeck et al (1996), even though they employed somewhat different indices of speed of information-processing. Our results are also compatible with those reported by Rabbitt and Maylor (1991) and Baddeley (1996), which also suggest that certain executive functions may be related to age, over and above any relationships with speed of processing and IQ.…”
Section: Relation To "Speed Of Processing"supporting
confidence: 79%
“…Thus, the relationship of age to performance on these tests was also not wholly secondary to changes in information-processing rate. The persistent relationship between age and the test of visuospatial paired associates learning is consistent with data reported by Nettelbeck and Rabbitt (1992) and by Nettelbeck et al (1996), even though they employed somewhat different indices of speed of information-processing. Our results are also compatible with those reported by Rabbitt and Maylor (1991) and Baddeley (1996), which also suggest that certain executive functions may be related to age, over and above any relationships with speed of processing and IQ.…”
Section: Relation To "Speed Of Processing"supporting
confidence: 79%
“…It appears that the role of speed of processing in remembering may be particularly important during rehearsal or encoding [18,24], as Salthouse [14] originally theorised.…”
Section: Speed Of Information Processingmentioning
confidence: 99%
“…For example, Royall and colleagues have recently demonstrated that among residents of a continuing-care retirement community, learning rate over trials on the CVLT predicts dementia type (Alzheimer's-type versus nonAlzheimer's type), but baseline cross-sectional performance did not (Royall, Palmer, Chiodo, & Polk, 2003). The authors suggest that performance on the CVLT learning trials Rabbitt, Wilson, & Batt (1996) who found using a serial learning task that initial recall and learning were statistically uncorrelated, and that initial recall was more strongly related to indices of processing speed.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…For example, Royall and colleagues have recently demonstrated that among residents of a continuing-care retirement community, learning rate over trials on the CVLT predicts dementia type (Alzheimer's-type versus nonAlzheimer's type), but baseline cross-sectional performance did not (Royall, Palmer, Chiodo, & Polk, 2003). The authors suggest that performance on the CVLT learning trials Rabbitt, Wilson, & Batt (1996) who found using a serial learning task that initial recall and learning were statistically uncorrelated, and that initial recall was more strongly related to indices of processing speed.Previous research has also highlighted other predictors of initial recall and learning (e.g., sociodemographic characteristics such as age, gender, race, and education, and health factors). With respect to age, a number of cross-sectional and longitudinal studies have found evidence of negative age differences and age-related decline performance on measures of episodic memory (see Bäckman, Small, Wahlin, & Larson, 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation